Penalized classification for optimal statistical selection of markers from high-throughput genotyping: application in sheep breeds. (24th October 2017) - Sottile, G.; Sardina, M. T.; Mastrangelo, S.; Di Gerlando, R.; Tolone, M.; Chiodi, M.; Portolano, B.
Abstract : The identification of individuals' breed of origin has several practical applications in livestock and is useful in different biological contexts such as conservation genetics, breeding and authentication of animal products. In this paper, penalized multinomial regression was applied to identify the minimum number of single nucleotide polymorphisms (SNPs) from high-throughput genotyping data for individual assignment to dairy sheep breeds reared in Sicily. The combined use of penalized multinomial regression and stability selection reduced the number of SNPs required to 48. A final validation step on an independent population was carried out obtaining 100% correctly classified individuals. The results using independent analysis, such as admixture, F st, principal component analysis and random forest, confirmed the ability of these methods in selecting distinctive markers. The identified SNPs may constitute a starting point for the development of a SNP based identification test as a tool for breed assignment and traceability of animal products.